GeneX Va: VBC open source microarray database and analysis software. (April 2004) - Lee, Jae K.; Laudeman, Tom; Kanter, Jodi; James, Teela; Siadaty, Mir S.; Knaus, William A.; Prorok, Alyson; Bao, Yongde; Freeman, Brad; Puiu, Daniela; Wen, Li min; Buck, Gregory A.; et al.
Developed by the Virginia Bioinformatics Consortium (VBC), GeneX Va is an open source, freeware database and bioinformatics analysis software for archiving and analyzing Affymetrix GeneChip ® data. It provides an integrated framework for management, documentation, and analysis of microarray experiments and data to support a range of users, from individual research laboratories to institutional microarray facilities. GeneX Va also provides web-based access to a PostgreSQL relational database system with a comprehensive security system. Data can be extracted from the database and delivered to interactive or scriptable statistical analysis protocols. The security system allows each investigator to manage their own array data and analysis output files and also provides custom access privileges for other users, groups, and internal/external collaborators. The analysis interface uses "Analysis Trees, " an innovative user interface that allows researchers to interactively create a tree-structured flow chart of analysis routines. The latest GeneX Va software is available from and can be freely downloaded at the Sourceforge web sitehttp://va-genex.sourceforge.net . To allow researchers to access the database and analysis capabilities of the GeneX Va system, microarray data from many VBC GeneChip experiments have been deposited into a public section of the GeneX Va system at the University of Virginia. The VBC GeneX Va sites, which include documentation, are athttp://genes.med.virginia.edu/ of the University of Virginia and athttp://genex.csbc.vcu.edu/ of the Virginia Commonwealth University.